Implementasi Transistor BD139 dan Rangkaian Relay pada Mesin Air - Raita Rahmatina; Muhammad Nor Aripin; Muhammad Ikbal; Agatha Deolika (Institut Shanti Bhuana, 2023)
The application of transistors to the water engine involves a set of relays that keep it in check for power stability as well. The purpose of this study is to prevent the water supply of tanks from filling out beyond capacity, so the workable solution is the installation of a device that indicates when the water is fully charged. That way the sprinkler will automatically shut down. The research method used is a descriptive method for describing and describing the transistor bd139 Experiments and observations were made in order to determine the efficiency of the transistor transistors. The effect of applying the transistor bd139 to the prototype of the home with the water tank, which is that the water engine will automatically turn off when the water tank is fully charged and the water engine will automatically turn on with an led light warning to stay off. At the time of testing, it may be known that this series has worked well according to design.